Contemporary Chechnya conflict – nation-liberation fight or terrorism - Donaj, Łukasz (Przegląd Strategiczny, 2011)
The events of 11 September 2001, bloody terrorist attacks in Middle East, Bali Island, Dubrovka, Madrid or London, like thousands of other terror acts, depict how difficult, complicated and, at the same time, dangerous and unexpected phenomenon we deal with. Terrorism can undoubtedly be labeled on of the most important global problem of the present world. In this article the author tries to bring the problem of the Chechnya conflict, which is – in the eyes of international public opinion – today regarded as Russia’s internal affair. NewYork terrorist attacks of 11 September helped the West to perceive this war as an element of international fight with Islamic fundamentalism.